2004
DOI: 10.1016/j.physletb.2004.07.049
|View full text |Cite
|
Sign up to set email alerts
|

Particle–antiparticle asymmetries of Λ production in hadron–nucleon collisions

Abstract: The particle-antiparticle asymmetries of Λ production in 250 GeV/c π ± , K ± , and p -nucleon collisions are studied with two model parametrizations of quark to Λ fragmentation functions. It is shown that the available data can be qualitatively explained by the calculated results in both the quark-diquark model and a pQCD based analysis of fragmentation functions. The differences in the two model predictions are significant for K ± beams, and high precision measurements of the asymmetries with detailed x F and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…A lively discussion is ongoing in this field in order to correctly interpret the available data for both hadronic collisions and semi-inclusive DIS (see, for example, Refs. [42,45,46,47,48,49]). …”
mentioning
confidence: 99%
“…A lively discussion is ongoing in this field in order to correctly interpret the available data for both hadronic collisions and semi-inclusive DIS (see, for example, Refs. [42,45,46,47,48,49]). …”
mentioning
confidence: 99%
“…Then the experimental processes and quantities that are sensitive to the sea content in the nucleus should enable us to discriminate different models. It was shown that the Λ/Λ ratio of production cross sections in semi-inclusive DIS (SIDIS) process is a physical quantity that is sensitive to the sea quark content of nucleons [29][30][31][32][33]. In Ref.…”
Section: Introductionmentioning
confidence: 99%